2020
DOI: 10.1002/star.201900206
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Physicochemical Properties of Starch from Waxy and Non‐Waxy Barley

Abstract: Barley flour is widely utilized in food and nonfood industries. Morphological, structural, and functional properties of starches extracted from waxy and non-waxy barley are investigated and compared in this work. The morphology of starch granules in waxy and non-waxy barley is similar while waxy barley has a higher proportion of A-type starch granules and a lower proportion of B-type starch granules than those of non-waxy barley. Compared with non-waxy barley starch, waxy barley starch shows higher amylopectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
(44 reference statements)
2
11
1
Order By: Relevance
“…One-way ANOVA showed that peak viscosities did not differ significantly between waxy and non-waxy genotypes ( p > 0.01). Contrary to the literature, the waxy genotypes tested in this study did not have the highest peak viscosities [ 14 , 23 , 24 ]. Indeed, the non-waxy genotype DH133529 had the highest peak viscosity and the waxy genotype DH140490 had the lowest.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…One-way ANOVA showed that peak viscosities did not differ significantly between waxy and non-waxy genotypes ( p > 0.01). Contrary to the literature, the waxy genotypes tested in this study did not have the highest peak viscosities [ 14 , 23 , 24 ]. Indeed, the non-waxy genotype DH133529 had the highest peak viscosity and the waxy genotype DH140490 had the lowest.…”
Section: Resultscontrasting
confidence: 99%
“…Starch composition influences the characteristics of cooked barley foods [ 23 ]. There are known genotypes with normal (17 to 28% amylose), waxy (0 to 10% amylose) and high amylose (>30% amylose).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starch was hydrolyzed by porcine pancreatic -amylase (PPA), Aspergillus niger amyloglucosidase (AAG) and hydrochloric acid (HCl) as previously described (Chen et al, 2020). The starch slurry was centrifuged at 5,000 ×g for 5 min after each hydrolysis stage and the supernatant was used to determine glucose content by using a glucose assay kit (K-GLUC, Megazyme, Bray, Ireland) according to the manufacturer's instruction.…”
Section: Hydrolysis Analysismentioning
confidence: 99%
“…Despite the differences in specific expression patterns and protein locations of GBSSII and GBSSI [3], the two genes encoding these proteins share high sequence similarity with almost 66% identical deduced amino acid sequences in wheat [3] and about 70% homology at the nucleotide sequence level in rice [4]. However, several different functional alleles or haplotypes [12][13][14] have been identified in the waxy gene (GBSSI) region and are associated with amylose content in rice and many other crops, such as maize [15], wheat [16], barley [17], and cassava [18,19], but research on the functional properties of GBSSII gene in crops is limited, particularly in rice. A recent study reported novel GBSSII haplotypes in rice through genome-wide identification and genetic variation analyses [20], but additional evolutionary analyses on this gene have not been performed.…”
Section: Introductionmentioning
confidence: 99%